A DESCRIPTIVE STUDY ON TEACHING VOCABULARY AT THE THIRD GRADE STUDENTS OF SD N 04 BEJEN IN 2010/2011 ACADEMIC YEAR - PRASETYO, DANANG TEGUH (2011)
This qualitative research aims at describing the process of teaching-learning vocabulary at the third grade students of SD N 04 Bejen, Karanganyar. It is conducted to describe the process, goal, material, and the method of teaching vocabulary, problem faced by the teacher, and the problem solving applied by the teacher at SD N 04 Bejen, Karanganyar. The writer gets the data of this research from event, informant, and document. The techniques of collecting data are the interview and observation. The data are information relating to the process of teaching-learning vocabulary, problems faced and problem solving applied by the teacher at SD N 04 Bejen, Karanganyar. The result of the analysis shows that the goals of teaching vocabulary are to improve and develop students' vocabulary. The methods applied by the teacher are Grammar Translation Method and Direct Method. The teacher faces several problems in teaching vocabulary, namely: class management, students' different ability, and different motivation of the students. The problems solving applied by teacher are by using group work to manage the number of students that overload, arranging the position of the students place in the class, and giving advices and motivation about the importance of their activity in vocabulary class.